Perilaku Pedagang di Sentra Ikan Bulak Surabaya dalam Perspektif Etika Bisnis Islam - Gusti Putra, Kevvin Marsellino; Cahyono, Hendry (Universitas Negeri Surabaya, 2020)
This research aims to determine the behavior of merchants in the Sentra Ikan Bulak Surabaya. This research uses qualitative methods with qualitative descriptive approaches. The data source used is primary data by conducting observation and interview process with merchants at the Sentra Ikan Bulak Surabaya. The results of this research indicate that the behavior of merchants at the Sentra Ikan Bulak Surabaya is in accordance with the principles contained in Islamic business ethics, including the principle of tauhid, the principle of balance, the principle of free-will. The principle of responsibility, and the principle of virtue.